Learning Motivation of Female Students in Physical Education, Sports, and Health Subjects through Playing Badminton Sports - Elzas, Elzas Nurajab; Budiman; Rusmana, Ruslan (Journal of Physical and Outdoor Education, 2023)
This study aims to determine the learning motivation of female students in learning physical education, sports and health through badminton games at SMAN 1 Simpenan. The research method used in this study is a quantitative descriptive method, while the data collection technique uses a questionnaire. In this study the population used in this study were all female students of class XI IPS SMAN 1 Simpenan Kab, Sukabumi, totaling 20 people. The sampling technique used was the purposive sampling technique. Referring to the sampling technique used, the number of samples in this study was 20 people. Based on the results of research that has been obtained by data analysis, the learning motivation of female students in learning physical education, sports and health through badminton sports at SMAN 1 Simpenan from 20 subjects. The results of this study indicate that the learning motivation of female students in learning physical education, sports and health through badminton sports at SMAN 1 Simpenan is in the "Medium" category, seen from the percentage table of 20 people there are 6 very high category with a percentage of 30%, 3 people in the high category with a percentage of 15%, 7 people in the medium category with a percentage of 35%, 2 people in the low category with a percentage of 10%.